Eficiencia de las medidas de bioseguridad adoptadas para la atención odontológica durante la pandemia por COVID-19 en América del Sur - Romero Rodríguez, Merly Yulissa (2023)
Dental care has been limited as a result of the outbreak of the rapidly spreading COVID19 epidemic, declared by the World Health Organization (WHO) as a public health emergency and therefore of worldwide concern; therefore, it is necessary to carry out a bibliographic research on the application of the good dental practices suggested by this organization to reduce the risk of cross-contagion to which the dentist and his team are exposed in daily practice, due to exposure to aerosols and contact with probably contaminated body fluids. The purpose of this study was to verify the efficiency of the biosecurity measures applied by dental personnel in South America during the COVID-19 pandemic. A documentary bibliographic study was carried out based on the analysis of 30 scientific articles in dentistry, published in the digital platforms Medline, PubMed and Google Scholar. The 30 papers selected met the inclusion and exclusion criteria previously established; the results revealed that there is regular knowledge among dental personnel, while the use of biosafety barriers is not fully complied with and waste is not adequately handled, which leads to the conclusion that there is not 100% efficiency in the protocol applied in patient care to prevent the spread of SARS-CoV-2